Effect of Spodoptera frugiperda on different growth stages of corn - Cruz, Ivan (2014)
Research was conducted in Lafayette, Indiana, USA, in 1978 and 1979 to study the effect of fall armyworm, Spodoptera frugiperda on corn productivity. Artificial infestation was made on five growth stages of corn: 4-6 leaves, 8-10 leaves, 12-14 leaves, tassel and silk. Infestation was achieved by placing one fall armyworm egg mass per plant. One egg mass contained approximately 50 eggs. A physical barrier was used to avoid movement of larvae between experimental plots. Parameters evaluated were leaf damage. 20 days after infestation, ear damage, ear length, grain weight and grain number. Based on the results it was concluded that the most susceptible stage of growth was the 8-10 leaf stage, that is, approximately 40 days from the planting time. Infestation at this stage caused an average yield reduction of 18.7 percent. An average yield reduction of 6.6, 7.6 and 8.6 percent was obtained from plots infested at the 4-6 leaf, tassel and 12-14 leaf stages, respectively. No yield reduction occured at the silking stage. An average reduction of 18.4 percent on the number of grain obtained from plots infested at the 8-10 leaf stage was the main factor contributing to the greater yield reduction in that plot.